Implementasi Program Kampus Merdeka (Studi Kasus Magang di Rumah Rakyat di Sekretariat Jenderal Dewan Perwakilan Rakyat Republik Indonesia) - Suprayitno Suprayitno; Mario Purnama Putra; Sri Mujiarti Ulfah (Jurnal Administrasi dan Kebijakan Publik, 2022)
Link and match not only with the industrial world but also with a future that is changing so fast. Universities are forced to design and implement innovative learning processes so that students can achieve learning achievements that include aspects of attitudes, knowledge, and skills optimally and always relevant so that the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Regulation no. 3 of 2020 concerning National Higher Education Standards to implement the Merdeka Campus Program policy with the aim of this program being able to develop the capacity of the nation's children in the world of education with 8 (eight) forms of activity in it so that the Secretariat General of the House of Representatives of the Republic of Indonesia organizes Internship activities at the People's House ( MDRR) The House of Representatives of the Republic of Indonesia (DPR RI) as a partner of the internship/work practice of the Merdeka Campus Program. The research method used in the descriptive qualitative research method. The results of the study show that the implementation of the independent campus program in internship activities at people's homes at the Secretariat General of the House of Representatives of the Republic of Indonesia has not been carried out properly. This is based on the existing indicators, related to communication experiencing problems with the lack of maximum communication transmission carried out by the implementer. Resources have not run optimally where the facilities in the Secretariat General of the DPR RI cannot be used optimally, then the independent campus website sometimes experiences system errors. The disposition or attitude of the implementers has not gone well, this is evident in the attitude of the implementers who delay the disbursement of pocket money and incentives as well as the difficulty of converting credits in several university campuses in Indonesia. Then the Standard Operating Procedure, in its implementation there is no SOP that regulates the procedure, but there is an Apprenticeship Curriculum at the People's House of the DPR RI as a reference in its implementation